Strengthening of traditional farming systems with small and large ruminants in arid region of Andhra Pradesh - KALYANI, D LAKSHMI; DEVA, SAHAJA; BABU, M VIJAYSANKAR; NATARAJ, K C; RAO, I BHASKAR; LAKSHMAN, K; REDDY, B SAHADEVA; PRASAD, J V N S (The Indian Journal of Animal Sciences, 2026)
The study explores the demonstrative performance of Livestock based Integrated Farming System (IFS) with different technologies or interventions under rainfed and partially irrigated conditions in farmers’ fields of Ananthapuramu district, Andhra Pradesh during 2023 and 2024. The objective of the study was to strengthening the traditional IFS system for marginal and small farm holdings, with small and large ruminants focusing on improving productivity, profitability and employment generation in arid region of Andhra Pradesh. A total of 36 farmers were selected and categorized into rainfed and partially irrigated farming situations. Various IFS models, including crop + small ruminants (CSR), crop + large ruminants (CLR) and crop + large + small ruminants (C + LR + SR) were demonstrated with and without scientific interventions. Improved management practices, such as use of high-yielding crop varieties, moisture conservation practices, drought mitigation techniques, nutritional feeding for livestock, perennial tree module and capacity building programmes were introduced. The results demonstrated that the IFS models with scientific interventions significantly increased yields, economic returns and employment opportunities compared to traditional farming systems. Specifically, net returns and productivity were markedly higher in the improved IFS models. The study concluded that integrating scientific agricultural practices within traditional IFS frameworks can substantially improve sustainability and economic viability of farming in scarce rainfall zone of Andhra Pradesh.